Sosialisasi dan Pelatihan Digital Marketing sebagai Bentuk Promosi terhadap Peningkatan Daya Tarik Konsumen pada Produk Lokal - Pambudi, Agung; Takarini, Nurjanti (Gayaku Publisher, 2023)
Local products in Indonesia are very diverse, but still underestimated by the Indonesian people assuming the quality is still not good. Digitalization of marketing applied in the promotion of local products will help change the stigma of the community on local products. Good and widespread promotion makes people know the quality offered so that consumer attraction can increase. MSME actors, most of whom are housewives, will find it difficult to penetrate digital marketing without assistance from other parties. The purpose of this service is to increase the skills possessed by MSME actors so that they can keep up with the times to penetrate digital marketing. Through this activity, it is expected to increase skills and increase knowledge to MSME players so that they can market their products more widely.